2015
DOI: 10.1016/j.ejca.2015.06.115
|View full text |Cite
|
Sign up to set email alerts
|

Results of a phase 1 trial combining ridaforolimus and MK-0752 in patients with advanced solid tumours

Abstract: Background The phosphatidylinositol 3-kinase/protein kinase-B/mammalian target of rapamycin (PI3K-AKT-mTOR) signaling pathway is aberrantly activated in several cancers. Notch signaling maintains cell proliferation, growth, and metabolism in part by driving the PI3K pathway. Combining the mTOR inhibitor ridaforolimus with the Notch inhibitor MK-0752 may increase blockade of the PI3K pathway. Methods This phase I dose-escalation study (NCT01295632) aimed to define the dose-limiting toxicities (DLTs) and maxim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(39 citation statements)
references
References 39 publications
1
38
0
Order By: Relevance
“…Further studies showed an association of Notch signaling activation with a poor prognosis in several cancers [37,38]. Thus, anti-DLL4/Notch signaling has become a new concept implicated in anti-angiogenic therapy of tumors [27,29]. The present study demonstrated the upregulation of Notch signaling core-components in HPC, suggesting a possible crucial role of this signaling pathway in hyper-angiogenesis in this tumor.…”
Section: Discussionsupporting
confidence: 64%
“…Further studies showed an association of Notch signaling activation with a poor prognosis in several cancers [37,38]. Thus, anti-DLL4/Notch signaling has become a new concept implicated in anti-angiogenic therapy of tumors [27,29]. The present study demonstrated the upregulation of Notch signaling core-components in HPC, suggesting a possible crucial role of this signaling pathway in hyper-angiogenesis in this tumor.…”
Section: Discussionsupporting
confidence: 64%
“…Early staged clinical trials assessing the efficacy of MK-0752 in combination with other drugs, such as MTOR inhibitors or chemotherapies, demonstrate that while gamma secretase inhibitors can limit CSC populations in preclinical studies, it is still challenging to completely eradicate CSC subgroups in clinical settings of head and neck squamous cell carcinoma (HNSCC) and pancreatic ductal adenocarcinoma (PDAC) [82, 83]. Complete response in these studies was only observed in 1 out of 15 patients with HNSCC (Table 3) [82]. Partial response was observed in 1 out of the 15 patients with HNSCC and 11 out of 18 patients with PDAC [82, 83].…”
Section: Signaling Pathways Of Csc Therapeutic Targetsmentioning
confidence: 99%
“…Complete response in these studies was only observed in 1 out of 15 patients with HNSCC (Table 3) [82]. Partial response was observed in 1 out of the 15 patients with HNSCC and 11 out of 18 patients with PDAC [82, 83]. While partial response was promising for the PDAC patients, time to subsequent disease progression was only 38 weeks, suggesting the need for more effective therapies.…”
Section: Signaling Pathways Of Csc Therapeutic Targetsmentioning
confidence: 99%
“…However, only a few solid tumour patients have experienced complete responses to selected drugs, including MK0752 (Krop et al , 2012; Piha-Paul et al , 2015) and PF03084014 (Messersmith et al , 2015). Moreover, many drugs induce a variety of severe adverse events such as intractable diarrhoea, vomiting, skin disorders and hypophosphatemia (Takebe et al , 2014), perhaps due to the wide distribution of the Notch pathway in normal tissues, especially NSCs.…”
Section: Clinical Targeted Therapymentioning
confidence: 99%